Affective Switch Associated With Oral, Low Dose Ketamine Treatment in a Patient With Treatment Resistant Bipolar I Depression. Case Report and Literature Review - Wilkowska, Alina; Szałach, Łukasz; Słupski, Jakub; Wielewicka, Aleksandra; Czarnota, Małgorzata; Gałuszko-Węgielnik, Maria; Wiglusz, Mariusz S.; Cubała, Wiesław J. (Frontiers in Psychiatry, 2020)
There is a growing evidence for the rapid and robust antidepressive effect of ketamine in unipolar and bipolar treatment resistant depression although evidence for the risk of affective switch is still limited. This case presents bipolar I disorder patient with treatment resistant depressive episode experiencing a switch to manic episode with mixed features shortly after receiving eight subanaesthetic doses of oral ketamine as an add-on treatment preceded by 2-day period of manic symptoms.